Subgrid corrections in finite-element modeling of storm-driven coastal flooding. (November 2021) - Woodruff, Johnathan L.; Dietrich, J.C.; Wirasaet, D.; Kennedy, A.B.; Bolster, D.; Silver, Z.; Medlin, S.D.; Kolar, R.L.
Abstract: Coastal flooding models are used to predict the timing and magnitude of inundation during storms, both for real-time forecasting and long-term design. However, there is a need for faster flooding predictions that also represent flow pathways and barriers at the scales of critical infrastructure. This need can be addressed via subgrid corrections, which use information at smaller scales to 'correct' the flow variables (water levels, current velocities) averaged over the mesh scale. Recent studies have shown a decrease in run time by 1 to 2 orders of magnitude, with the ability to decrease further if the model time step is also increased. In this study, subgrid corrections are added to a widely used, finite-element-based, shallow water model to better understand how they can improve the accuracy and efficiency of inundation predictions. The performance of the model, with and without subgrid corrections, is evaluated on scenarios of tidal flooding in a synthetic domain and a small bay in Massachusetts, as well as a scenario with a real atmospheric forcing and storm surge in southwest Louisiana. In these tests we observed that the subgrid corrections can increase model speed by 10 to 50 times, while still representing flow through channels below the mesh scale to inland locations. Highlights: Coastal flooding may be controlled by flow channels and barriers at very small scales. These flow features can be represented at the mesh scale with subgrid corrections. ADCIRC model was corrected for subgrid flows in tide and storm surge predictions. Close matches to peak water levels with models that are 65 times coarser than before. Significant speed-ups will allow for faster predictions and ensemble forecasts.